SAPCC1G2 : a mutual authentication protocol promote the security of RFID and WSN integration system. (7th September 2011) - Rong, Jifang; Huang, Shengye
With the integration of radio frequency identification (RFID) and wireless sensor network, these two technologies are used more and more extensively. The security issues of the integration system are increasingly concerned by people, and the security of RFID is the most critical part of the integration system. EPC C1G2 is a standard for low-cost RFID air interface. The authentication processes of most existing RFID systems are not compatible with the EPC C1G2 standard. This paper proposes a secure authentication protocol conforming to EPC C1G2, called SAPCC1G2, which is compatible with existing RFID reader and achieves the data dynamic updating in transmission process. The new scheme can defend typical attacks such as tracking, replaying, eavesdropping, cloning and denial of service attack. It has higher security and quicker authentication speed, so it has advantages over existing peers. It can promote the security and the efficiency of the authentication process for the integrated system.